The political perils of Cold War foreign relations: Adlai Stevenson’s democrats and foreign policy in the 1956 presidential election - Sewell, Bevan (Taylor & Francis, 2017)
This article uses the case of the 1956 presidential election between Adlai Stevenson and Dwight Eisenhower to highlight the ways that an obsession with foreign relations could, in fact, prove problematic to a campaign. Focusing primarily on Stevenson’s advisors, it argues that long-standing problems in the Democrats’ strategy on foreign relations, coupled with the emotional attachments that several key advisors had toward the issue, combined to ensure that the Democrats failed to develop an effective foreign policy platform for the 1956 election (particularly when running against a president who was believed to be so successful in that arena). Ultimately, it argues that the Stevenson campaign’s failure to forge an effective position highlights the problematic relationship between domestic policies and foreign relations.